2018
DOI: 10.1016/j.jnoncrysol.2018.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Melting behaviour of raw materials and recycled stone wool waste

Abstract: Stone wool is a widely used material for building insulation, to provide thermal comfort along with fire stability and acoustic comfort for all types of buildings. Stone wool waste generated either during production or during renovation or demolition of buildings can be recycled back into the stone wool melt production. This study investigates and compares the thermal response and melting behaviour of a conventional stone wool charge and stone wool waste. The study combines differential scanning calorimetry (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This method is an effective way to lower the raw material cost by replacing coke usage. Moreover, a recent study compared the melting behavior of virgin raw materials and waste rock wool and concluded that re-melting the waste rock wool is 23% more energy-efficient on differential scanning calorimetry (DSC) [ 31 ].…”
Section: Waste Characterizationsmentioning
confidence: 99%
See 3 more Smart Citations
“…This method is an effective way to lower the raw material cost by replacing coke usage. Moreover, a recent study compared the melting behavior of virgin raw materials and waste rock wool and concluded that re-melting the waste rock wool is 23% more energy-efficient on differential scanning calorimetry (DSC) [ 31 ].…”
Section: Waste Characterizationsmentioning
confidence: 99%
“…Each rock wool factory uses different raw materials based on their preference and intended use. Nevertheless, the raw material is typically from the rock crystalline group and may include anorthosite, dolomite, diabase, olivine sand, or even slag [ 31 ]. Table 2 shows the compositions of chemicals of ordinary waste rock wool from different research studies.…”
Section: Waste Characterizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…DSC has a wide spectrum of applications ranging from simple heat of fusion evaluation() to advanced material microstructural evolution analyses and complex chemical reaction process identification . The versatility of the DSC is vast and researchers apply it to assess: coal,() cjceass,() waste,() catalysts,() minerals,() cement,() ceramics,() alloys,() and polymers. () Applications include: gasification,() pyrolysis,() combustion,() adsorption,() desorption,() calcination,() dehydration,() thermal stability,() phase transitions,() phase diagrams,() polymer crystallization,() glass transition, curing time, and reaction kinetics …”
Section: Applicationsmentioning
confidence: 99%